Pengaruh Sikap Belajar, Pengelolaan Kelas dan Model Pembelajaran Meaningfull Instructional Design Terhadap Gemar Belajar dari 7 (Tujuh) Kebiasaan Anak Indonesia Hebat pada Kelas XI B SMA Negeri 10 Tana Toraja - Gayang, Sertika Arruan; Syarifuddin, Syarifuddin; W, Muhammad Fahreza (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
This study aims to: 1). To determine and analyze the influence of learning attitudes on the love of learning based on 7 (Seven) Habits of Great Indonesian Children in Grade XI B of SMA Negeri 10 Tana Toraja. 2). To determine and analyze the influence of classroom management on the love of learning based on 7 (Seven) Habits of Great Indonesian Children in Grade XI B of SMA Negeri 10 Tana Toraja. 3). To determine and analyze the influence of the Meaningful Instructional Design Learning Model on the Love of Learning based on 7 (Seven) Habits of Great Indonesian Children in Grade XI B of SMA Negeri 10 Tana Toraja. 4). To determine and analyze the influence of learning attitudes, class management and the Meaningful Instructional Design learning model simultaneously on the love of learning from the 7 (seven) habits of great Indonesian children in class XI B of SMA Negeri 10 Tana Toraja. This research approach uses quantitative research. The study was conducted on 40 students of class XI B of SMA Negeri 10 Tana Toraja. The population in this study was 40 students studying Economics. The sampling technique used was Saturated Sampling, meaning the population is equal to the sample, so the sample size was 40 students. The data collection technique used a questionnaire and the data analysis technique used multiple regression techniques and t-test and F-test analysis using SPSS 26. The results of this study are: 1). Learning Attitude has a positive and significant effect on the variable Love of Learning. 2). Class Management (X2) has a positive and significant effect on the variable Love of Learning. 3). The Meaningful Instructional Design Learning Model (X3) has a positive and significant effect on the variable Love of Learning and 4). The sig. value of the F test is 0.000 at a significance level of 0.05. This value is less than 0.05, indicating that all independent variables, namely Learning Attitude (X1), Class Management (X2), and the Meaningful Instructional Design Learning Model (X3), jointly influence Love of Learning (Y) in class XI B students of SMA Negeri 10 Tana Toraja.